Handbook of research on challenges and risks involved in deploying 6G and NextGen networks - Alhadidi, Basim; Bharathy, A M Viswa (IGI Global, 2022)
Challenges and risks involved in deploying 6G and NextGen networks explores strategies for the design and deployment of more secured and user-centered NextGen networks through artificial intelligence to enrich user experience. It further investigates the political, social, and geographical challenges involved in realizing these 6G networks and explores ways to improve the security of future potential applications as well as protect user data from illegal access. Covering topics such as deep learning algorithms, aerial network communication, and edge computing, this major reference work is an indispensable resource for regulatory and policy groups, associations and technology groups, government and international bodies, technology executives and technical institutions, management consulting and advisory firms, communication engineers, network engineers, students and educators of higher education, researchers, and academicians